Protection Of Indonesian Cultural Heritage Through Sui Generis Law - Susanti, Diah Imaningrum; Susriyani, Rini (Advances in Social Sciences Research Journal, 2019)
Indonesia‘s copyright law is inadequate to protect Traditional Cultural Expression (TCE) because moral right and economic rights in copyright law cannot be applied to TCE. The State/Government as copyright holder of TCE is also a false concept as it is a political entity that has no right to hold the moral and economic rights. Regulating TCE in different laws raises ―overlapping‖ legal consequences. A sui generis law might be more appropriate for cultural heritage protection as it specifies the policy objectives, subject matter, criteria, the owner of the rights, the kind of and the way the rights are adminsitered and enforced, as well as when the rights are lost and expire.